Strategic Information System Design for Enhancing Executive Decision-Making in the Retail Sector - Eko Purwanto; Nurrohman (Telkom University, 2026)
In the rapidly evolving retail industry, executives are increasingly challenged to make timely and accurate decisions based on complex and dynamic data. This study aims to design a strategic information system (SIS) that can support executive-level decision-making by integrating key business intelligence components. The proposed system is developed using a user-centered approach and incorporates a web-based dashboard that visualizes real-time sales, inventory, and customer behavior analytics. Through a case study at a medium-sized retail company, the system was evaluated based on its usability, effectiveness, and impact on decision quality. The results demonstrate that the implementation of the SIS significantly improves the speed and accuracy of executive decisions, particularly in areas related to inventory control, sales forecasting, and strategic planning. This research contributes to the advancement of digital decision-support tools in the retail business environment and provides a model that can be replicated in similar organizational contexts.